2004
DOI: 10.1186/1471-2229-4-10
|View full text |Cite
|
Sign up to set email alerts
|

The roles of segmental and tandem gene duplication in the evolution of large gene families in Arabidopsis thaliana

Abstract: Background: Most genes in Arabidopsis thaliana are members of gene families. How do the members of gene families arise, and how are gene family copy numbers maintained? Some gene families may evolve primarily through tandem duplication and high rates of birth and death in clusters, and others through infrequent polyploidy or large-scale segmental duplications and subsequent losses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

48
926
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 1,631 publications
(1,095 citation statements)
references
References 82 publications
48
926
0
Order By: Relevance
“…Among them, the segmental duplication associated with the salicoid duplication event that occurred 65 million years (Ma) ago significantly contribute to the amplification of many multi-gene families [61,69-71]. To determine the possible relationship between the NAC genes and potential segmental duplications, we mapped Populus NACs to the duplicated blocks established in the previous studies [5].…”
Section: Resultsmentioning
confidence: 99%
“…Among them, the segmental duplication associated with the salicoid duplication event that occurred 65 million years (Ma) ago significantly contribute to the amplification of many multi-gene families [61,69-71]. To determine the possible relationship between the NAC genes and potential segmental duplications, we mapped Populus NACs to the duplicated blocks established in the previous studies [5].…”
Section: Resultsmentioning
confidence: 99%
“…The much more numerous Group III WRKY genes in Arabidopsis and rice is explained by tandem duplication and recent duplication events, which has led to a large-scale expansion of the gene families in these genomes [31,35]. Recent gene duplication and tandem duplication events are the most important factors in the rapid expansion and evolution of gene families [35]. Previous research has demonstrated that the Arabidopsis Group III WRKY gene family expanded rapidly as a result of recent segmentaland tandem duplication events.…”
Section: Number and Type Of Sesame Wrky Genesmentioning
confidence: 99%
“…Table 3 shows that one key difference between the sesame, Arabidopsis, and rice genomes is the number of Group III WRKY genes in each. The much more numerous Group III WRKY genes in Arabidopsis and rice is explained by tandem duplication and recent duplication events, which has led to a large-scale expansion of the gene families in these genomes [31,35]. Recent gene duplication and tandem duplication events are the most important factors in the rapid expansion and evolution of gene families [35].…”
Section: Number and Type Of Sesame Wrky Genesmentioning
confidence: 99%
“…Our results suggest that the current ncRNA annotation of plant genomes, which is still based in a large part on comparative genomics, may miss several thousand ncRNA families that appeared more recently than the divergence time from species used for comparison. The fact that 80% of the ncRNA families detected in our intragenome screen are associated to tandem rather than segmental duplications further supports a recent occurrence of many ncRNA repeats, as there are more recent events of tandem duplications than of segmental duplications (Cannon et al 2004).…”
Section: Discussionmentioning
confidence: 79%